IMPLEMENTASI PEMBELAJARAN BAHASA JAWA SD YANG INTEGRATIF KOMUNIKATIF BERBASIS FOLKLORE LISAN SEBAGAI WUJUD KONSERVASI BUDAYA - Kurniati, Endang (Universitas Negeri Semarang, 2015)
This research objective was to disseminate and to test the effectiveness of the design of integrative communicative Javanese language learning inÂ elementary school based on verbal folklore as a form of cultural conservation.Â This research used experimental research method. The subjects of this researchÂ were elementary school teachers and students in Semarang and Banyumas. TheÂ result of this research showed that this learning design was effective. The studentsâÂ result of study in experimental class was better compared with control class andÂ studentsâ performance in experimental class during the learning process wasÂ more active, enthusiastic, and creative. According to the teachers, this learningÂ besides teaching language, art, and culture was also educating character asÂ well. Moreover, this learning was as alternative of Javanese culture preservation.Keywords: integratif, komunikatif, folklore lisan, konservasi budaya